An overview of the role of platelets in angiogenesis, apoptosis and autophagy in chronic myeloid leukaemia - Lisa Repsold; Roger Pool; Mohammed Karodia; Gregory Tintinger; Annie Margaretha Joubert (Cancer Cell International, 2017)
Abstract Amongst males, leukaemia is the most common cause of cancer-related death in individuals younger than 40 years of age whereas in female children and adolescents, leukaemia is the most common cause of cancer-related death. Chronic myeloid leukaemia (CML) is a chronic leukaemia of the haematopoietic stem cells affecting mostly adults. The disease results from a translocation of the Philadelphia chromosome in stem cells of the bone marrow. CML patients usually present with mild to moderate anaemia and with decreased, normal, or increased platelet counts. CML represents 0.5% of all new cancer cases in the United States (2016). In 2016, an estimated 1070 people would die of this disease in the United States. Platelets serve as a means for tumours to increase growth and to provide physical- and mechanical support to elude the immune system and to metastasize. Currently there is no literature available on the role that platelets play in CML progression, despite literature reporting the fact that platelet count and size are affected. Resistance to CML treatment with tyrosine kinase inhibitors can be as a result of acquired resistance ensuing from mutations in the tyrosine kinase domains, loss of response or poor tolerance. In CML this resistance has recently become linked to bone marrow (BM) angiogenesis which aids in the growth and survival of leukaemia cells. The discovery of the lungs as a site of haematopoietic progenitors, suggests that CML resistance is not localized to the bone marrow and that the mutations leading to the disease and resistance to treatment may also occur in the haematopoietic progenitors in the lungs. In conclusion, platelets are significantly affected during CML progression and treatment. Investigation into the role that platelets play in CML progression is vital including how treatment affects the cell death mechanisms of platelets.